The planets - Wilberforce, Bert (2021)
"For many years, people believed there were nine planets that orbited the sun. Now we say there are eight. What happened to the ninth planet, Pluto? What are the different planets like? And what exactly makes a planet a planet? These are the many intriguing questions answered in this high-interest book, crafted to be accessible for readers of all levels. Young astronomers will be especially fascinated by the stunning photographs and Make the Grade fact boxes featured throughout the comprehensible text"--
Our eight planets -- What is a planet? -- The rocky planets -- The gas giants -- The ice giants -- Planetary explorations -- Outside out solar system -- How far from the sun?.
Includes bibliographical references and index.
Keywords: Planets -- Juvenile literature